Delivering value-for-money in PPPs? Risks and insights in change management. (June 2017) - McCann, Steven
A fundamental benefit sought from Public Private Partnerships is risk transfer – or more explicit allocation of risks between the public and private partners. However, not all operating risks can be transferred or eliminated. The public partner retains residual risk and remains ultimately accountable for the delivery of public services. Sub-standard management of major change events can lead to poor value-for-money outcomes. In-depth insights are provided in this article into how the actual management of Public Private Partnerships may be carried out and dealt with by governments at critical junctures during the concession period. Key risks, issues and critical success factors are identified that can have profound effects on the achievement of intended outcomes. These considerations build upon existing knowledge, policy and guidance for Public Private Partnerships, both nationally and internationally, making this essay tangible and grounded for both academics and practitioners.